A Systematic Analysis of Physicochemical and ADME Properties of All Small Molecule Kinase Inhibitors Approved by US FDA from January 2001 to October 2015 - O`Brien, Zhihong; F. Moghaddam, Mehran (Current Medicinal Chemistry, 2017)
Background: During lead identification and optimization, the advancement criteria may be driven based on scientific principles, prior experiences, and/or by examining the path paved by approved drugs. However, accessing the discovery data on physicochemical and ADME properties of the approved kinase inhibitors is a monumental task as these are either scattered in the literature or have not been published. Objective: Our goals were: 1) To compile the relevant data on all kinase inhibitors approved prior to 2016 for easy access by the biopharmaceutical community, 2) To provide a retrospective analysis to highlight trends and attributes which may have contributed to the “developability” of these drugs, and 3) To ignite focused debates on what constitutes “actionable”, “nice-to-have”, and unnecessary data. Such debates bring about more clarity on stage appropriateness of different types of information and prevent confusion due to abundance of unnecessary data, leading to more efficient and less costly drug discovery programs. Methods: A careful and thorough analysis of different bodies of data such as published manuscripts, and available regulatory documents were employed. Results: We were able to assemble a large body of data on the first thirty kinase inhibitors approved by US FDA since 2001. Conclusion: In conclusion, we have compiled physicochemical and ADME data on the first 30 approved kinase inhibitors and provided our retrospective analysis, which we hope is helpful in constructing advancement criteria in discovery programs. The examination of this data provides an opportunity to develop an opinion on data prioritization and stage appropriateness of assays.
Keywords: approved